2018
DOI: 10.1002/adfm.201804802
|View full text |Cite
|
Sign up to set email alerts
|

Trapped Photons Induced Ultrahigh External Quantum Efficiency and Photoresponsivity in Hybrid Graphene/Metal‐Organic Framework Broadband Wearable Photodetectors

Abstract: Metal‐organic frameworks (MOFs) have recently emerged as attractive materials for their tunable properties, which have been utilized for diverse applications including sensors, gas storage, and drug delivery. However, the high porosity and poor electrical conductivity of MOFs restrict their optoelectronic applications. Owing to the inherent tunability, a broadband photon absorbing MOF can be designed. Combining the superior properties of the MOFs along with ultrahigh carrier mobility of graphene, for the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 79 publications
2
64
0
Order By: Relevance
“…Besides, MOFs consisting of metallic ions and organic ligands have attracted much attention due to their fascinating architectures and their tunable physicochemical properties, which provide a new platform to develop optoelectronic devices. [103] Chen et al [104] reported a broadband wearable photodetector based on graphene/MOFs hybrid structure by a simple spin-coating method (Figure 6b). Besides, epitaxial alignment of 2D materials on the surface of 3D bulk is expected to facilitate low-defect interfaces and efficient vertical transport through 2D-3D heterostructures.…”
Section: D-3d MD Heterostructurementioning
confidence: 99%
“…Besides, MOFs consisting of metallic ions and organic ligands have attracted much attention due to their fascinating architectures and their tunable physicochemical properties, which provide a new platform to develop optoelectronic devices. [103] Chen et al [104] reported a broadband wearable photodetector based on graphene/MOFs hybrid structure by a simple spin-coating method (Figure 6b). Besides, epitaxial alignment of 2D materials on the surface of 3D bulk is expected to facilitate low-defect interfaces and efficient vertical transport through 2D-3D heterostructures.…”
Section: D-3d MD Heterostructurementioning
confidence: 99%
“…In the present work, a novel strategy was proposed by utilizing metal-organic frameworks (MOFs) nanoparticles as the photo-sensitive materials of 2DLM-based photodetectors. MOFs formed by the coordination of metal ions and organic ligands exhibit highly tailorable bandgap, optical absorbance and electrical conductivity through varying the metal, ligand, and/or the growth conditions [22][23][24][25][26][27][28], which can be applied to different situations in line with the requirements of detection bands. Among them, MOF (Ni-CAT-1) possesses a narrow bandgap of 0.48 eV and strong optical absorption in the SWIR region [29,30], making it appropriate to combine with 2DLM to achieve high-performance SWIR photodetection.…”
Section: Introductionmentioning
confidence: 99%
“…[ 26 ] For many applications requiring electrical contacts and/or exploitation of MOF optical properties, [ 27 ] MOF thin films are required. [ 28 , 29 , 30 , 31 ] Indeed, recent work demonstrated that monolithic, uniform, and compact MOF thin films show excellent photoresponse photoconductive and photodetector applications. One example is a porphyrinic MOF, where the donor–acceptor interaction with fullerene guest enhanced charge separation and yielded high photocurrent.…”
Section: Introductionmentioning
confidence: 99%